Gender differences in the prevalence and correlates of COVID-19 fear among mental health professionals: a network perspective based on a national survey in China - Shu-Ying Rao; Shu-Ying Rao; Mu-Rui Zheng; Mu-Rui Zheng; Feng-Rong An; Yuan Feng; Zhaohui Su; Teris Cheung; Gabor S. Ungvari; Gabor S. Ungvari; Chee H. Ng; Yu-Tao Xiang; et al. (Frontiers in Psychiatry)
BackgroundGender differences in COVID-19-related fear among mental health professionals (MHPs) have been inadequately studied. This study compared the gender differences in prevalence, correlates and network structure of COVID-19 fear among MHPs in China in the post-pandemic era.MethodsA nationwide cross-sectional study was conducted between January 22 and February 10, 2023. Binary logistic regression was used to identify factors associated with COVID-19 fear. Expected Influence was used to identify the most central (influential) symptoms in gender-specific networks, while network comparison tests were conducted to assess the differences between male and female models.ResultsAmong 7,199 MHPs, the overall prevalence of COVID-19 fear was 63.5% (95% CI: 62.3%-64.6%), with 61.7% (95% CI: 58.9%-64.4%) in males and 65.0% (95% CI: 63.7%-66.2%) in females. For male MHPs, factors associated with COVID-19 fear included having married status (OR: 1.39; 95% CI: 1.02–1.90; P = 0.037), poorer economic status (poor vs. good: OR: 1.91; 95% CI: 1.23–2.98; P = 0.004), more severe insomnia (OR: 1.04; 95% CI: 1.01–1.07; P = 0.018), and depression (OR: 1.09; 95% CI: 1.05–1.12; P < 0.001). For female MHPs, the significant factors included having married status (OR: 1.21; 95% CI: 1.06–1.37; P = 0.004), poorer economic status (poor vs. good: OR: 1.39; 95% CI: 1.11–1.73; P = 0.004), more severe insomnia (OR: 1.05; 95% CI: 1.03–1.06; P < 0.001), depression (OR: 1.09; 95% CI: 1.08–1.11; P < 0.001), and quarantine experience (OR: 1.17; 95% CI: 1.04–1.30; P = 0.006). Network analysis revealed that the most central symptom in the male network was FOC6 (sleep difficulties due to COVID-19 concerns), while the corresponding node in the female network model was FOC7 (palpitations when thinking about COVID-19).ConclusionCOVID-19-related fear was more prevalent among female MHPs than males. Specific interventions targeting the central symptoms in each network should be implemented to alleviate COVID-19 fear effectively and improve the mental health of MHPs in the post-pandemic era.